Оценка колебаний системы турбоагрегат-фундамент-основание при сейсмических воздействиях - Шульженко, Николай Григорьевич; Гонтаровский, Павел Петрович; Гармаш, Наталия Григорьевна; Глядя, Алла Александровна (НТУ "ХПИ", 2017)
С использованием созданной расчетной методики проведена оценка колебаний системы турбоагрегат-фундамент-основание мощных турбоагрегатов при сейсмических воздействиях. Расчетная модель динамической системы состоит из произвольно ориентированных стержней и сосредоточенных масс. В стержневых конечных элементах с распределенными параметрами учитываются все виды деформаций, имеющие место при колебаниях стержней. Воздействие сейсмической нагрузки моделируется с использованием акселерограмм реальных землетрясений. Проведен анализ частот и форм собственных колебаний динамических систем. Получены спектральные характеристики используемых сейсмограмм.

Vibration Parameters of the turbounit-foundation-base system of powerful turbine units exposed to seismic loads were evaluated using the computation technique and the software developed on the basis of the method of finite elements. The computation model of dynamic system that allows us to take into consideration the structural peculiarities of basic elements consists of arbitrary oriented rodsand concentrated masses with the moments of inertia interconnected by rigid or linear and nonlinear elastically damped elements. Rod-type finite elements with distributed parameters take into account all the types of strains caused by rod oscillations. The seismic load action is simulated using the accelerograms of real earthquakes. The mode shape and self-oscillation modes of turbounit-foundation-base system have been analyzed. Spectral characteristics of the seismograms used have been defined. It has been established that the seismic loading pattern considerably affects the stress of individual system elements even at the same earthquake intensity. To estimate the seismic resistance spatial computation models were used to take into consideration the structural specific features of turbounit-foundation-base system and seismic loads should be considered in the three mutually perpendicular axes. The obtained research data can be used for the design of powerful turbine units to evaluate their seismic resistance.
Estimating the vibrations of turbounit-foundation-base system exposed to seismic loads
Keywords: колебания; акселерограмма; ТФО; упруго-демпферные связи; цилиндр низкого давления; ЦНД; oscillations; foundation; accelerogram